Technical and economic indicators of milk production systems in the Caiuá sandstone region - Simony Marta Bernardo Lugão; Bruno Volsi; Gustavo Vaz da Costa; Edson Luiz Diogo de Almeida; Tiago Santos Telles (Acta Scientiarum. Animal Sciences, 2018)
The aim of this study was to analyze technical and economic indicators of family milk production systems, with different technology levels, in the Caiuá sandstone area in Northwestern Paraná, Brazil. The analysis period covers the agricultural years 2002/2003 to 2013/2014. The categorization of the milk production systems was based on information from agricultural farms monitored by the Reference Network for Family Agriculture. The cost-benefit analysis method was used for the economic assessment of milk production. Based on the results, three family milk production systems were identified in the region, characterized by the use of low, medium and high intensification technologies for pasture management. The production costs per unit area were found to be higher in the system with high technology and lower in the system with low technology. However, although the total revenue in the production system with a high technological intensification is greater than in the other systems, the capital needed for a technological transition is higher. In all the systems, when the costs were deducted, including the return on family labor, there was a profit, even with the climate and soil constraints inherent in the region.